Selective CDK6 degradation mediated by cereblon, VHL, and novel IAP-recruiting PROTACs. Issue 9 (1st May 2020) - Anderson, Niall A.; Cryan, Jenni; Ahmed, Adil; Dai, Han; McGonagle, Grant A.; Rozier, Christine; Benowitz, Andrew B.
Abstract: Inhibitors of CDK4 and CDK6 have emerged as important FDA-approved treatment options for breast cancer patients. The properties and pharmacology of CDK4/6 inhibitor medicines have been extensively profiled, and investigations into the degradation of these targets via a PROTAC strategy have also been reported. PROTACs are a novel class of small-molecules that offer the potential for differentiated pharmacology compared to traditional inhibitors by redirecting the cellular ubiquitin–proteasome system to degrade target proteins of interest. We report here the preparation of palbociclib-based PROTACs that incorporate binders for three different E3 ligases, including a novel IAP-binder, which effectively degrade CDK4 and CDK6 in cells. In addition, we show that the palbociclib-based PROTACs in this study that recruit different E3 ligases all exhibit preferential CDK6 vs. CDK4 degradation selectivity despite employing a selection of linkers between the target binder and the E3 ligase binder.